Antioxidant Activity Test of Ethanolic Extract of Tempuyung Leaves (Sonchus Arvensis L.) Based on Linoleic - Thiocyanic Method - Suprijono, Agus; Sulistiani, Dian; Purwadi, Sarosa (Jurnal Akademika Kimia, 2023)
Free radicals chemically have free electrons, free radicals tend to take electrons from other molecules, which then give rise to abnormal compounds. Antioxidants are substances that can delay or prevent free radical oxidation reactions in lipid oxidation. Tempuyung leaves contain flavonoids which can act as antioxidants. This research aims to determine the antioxidant activity of the ethanol extract of tempuyung leaves using the linoleic-thiocyanate method and to determine the total phenolic and total flavonoid content using the Folin-Chiocalteu reagent method. The results showed that the ethanol extract of tempuyung leaf extract had antioxidant activity. Percentage of antioxidant activity of 10 % extract = 82.91 %, 5 % extract = 70.07 %, 1 % extract = 57.70 %, Vitamin E 1 % = 70.2 1%. Total phenolic content of 10% extract = 0.48 %, 5 % extract = 0.25 % and 1 % extract = 0.04 %. The total flavonoid content of the extract is 10 % = 0.14 %, 5 % extract = 0.07 %, and 1 % extract = 0.02 %. Pearson correlation test showed that phenolic and flavonoid compounds greatly influenced the antioxidant activity of the ethanol extract of tempuyung leaves.